Theoretical evaluation of the equivalent torsional rigidity of a unique GFRP-metal box-truss composite girder. (February 2022) - Zhang, Dongdong; Mo, Changjin; Gao, Yifeng; Yuan, Hui; Li, Fei; Zhao, Qilin; Yang, Jun
Abstract: A new type of glass fiber-reinforced polymer (GFRP)-metal space truss girder with a closed box-shaped cross section was designed for a lightweight deployable bridge. As a new structure, a design-oriented theoretical formulation on torsional rigidity is necessary to facilitate the practical design of the box-truss composite girder. In this study, a theoretical model was first established, with the aid of a homogenization concept and shear equivalence principle, to evaluate the equivalent torsional rigidity of the unique box-truss composite girder with multi-separated truss elements. Subsequently, a finite element model of a simply-supported 24-m girder subjected to unsymmetrical off-axis loadings was constructed and compared against existing experimental results whilst demonstrating good agreement. Based on the verified finite element method, a 72-m cantilever beam model applied with end pure torque was constructed to obtain the pure torsional rigidity of the box-truss composite girder and compared against the theoretical solutions, and good agreement was demonstrated. Comparisons indicated that the established equivalent theoretical model and finite element method could be fully used to calculate the torsional rigidity of the unique box-truss composite girder with satisfactory accuracy in the design procedures .